Incretin‐Based Therapies as Cardiometabolic Interventions: Outcome Hierarchy, Receptor‐Network Pharmacology and Phenotype‐Based Clinical Positioning - Ferenc Sztanek; Hajnalka Lőrincz; Mariann Harangi; Attila Csaba Nagy (Diabetes, Obesity and Metabolism, 2026)
ABSTRACT Aims Incretin‐based pharmacotherapy was initially developed to improve glucose‐dependent insulin secretion and glycaemic control in type 2 diabetes, but its clinical interpretation has expanded substantially with cardiovascular outcome trials, kidney outcome data, obesity studies and next‐generation polyagonist development. This narrative clinical review uses structured literature identification and outcome‐stratified synthesis to evaluate incretin‐based therapies as cardiometabolic interventions across diabetes, obesity, cardiovascular disease and chronic kidney disease. Materials and Methods The available evidence was interpreted according to therapeutic class, clinical domain, outcome maturity and safety boundaries, integrating clinical outcome evidence with receptor‐network pharmacology. Results Selected GLP‐1 receptor agonists are supported by hard cardiovascular and renal outcome data, whereas several dual, triple, amylin‐linked and oral small‐molecule strategies are currently supported mainly by glycaemic, weight‐loss, metabolic or early translational endpoints. This distinction is clinically important because treatment positioning should depend on patient phenotype, outcome maturity and safety boundaries rather than mechanistic plausibility alone. In patients with type 2 diabetes and established atherosclerotic cardiovascular disease, GLP‐1 receptor agonists with proven cardiovascular outcome benefit should be prioritised when atherosclerotic risk reduction is a major treatment goal. In type 2 diabetes with chronic kidney disease, semaglutide has dedicated kidney outcome evidence. In obesity with cardiometabolic risk, high‐magnitude and sustained weight reduction has become a clinically relevant therapeutic target. Receptor‐network pharmacology, including GLP‐1, GIP, glucagon and amylin receptor signalling, provides a useful explanatory framework for heterogeneous efficacy, tolerability and tissue‐level effects. Conclusions However, clinical use remains bounded by gastrointestinal tolerability, lean‐mass preservation, treatment durability, discontinuation effects and long‐term safety. This review therefore proposes phenotype‐based clinical positioning rather than a prescriptive treatment algorithm.